Syndromic diagnostic testing: a new way to approach patient care in the treatment of infectious diseases. (23rd September 2021) - Dumkow, Lisa E; Worden, Lacy J; Rao, Sonia N
Abstract: Advanced microbiology technologies such as multiplex molecular assays (i.e. syndromic diagnostic tests) are a novel approach to the rapid diagnosis of common infectious diseases. As the global burden of antimicrobial resistance continues to rise, the judicious use of antimicrobials is of utmost importance. Syndromic panels are now being recognized in some clinical practice guidelines as a 'game-changer' in the diagnosis of infectious diseases. These syndromic panels, if implemented thoughtfully and interpreted carefully, have the potential to improve patient outcomes through improved clinical decision making, optimized laboratory workflow, and enhanced antimicrobial stewardship. This paper reviews the potential benefits of and considerations regarding various infectious diseases syndromic panels, and highlights how to maximize impact through collaboration between clinical microbiology laboratory and antimicrobial stewardship programmes.